(untitled) (CAHIERS MAGELLANES-NS, 2024)
The choice of the posts materials which are used in dentistry in the restoration procedures challenges the longevity of treatment. The two most used types of dental posts and cores are glass fiber posts and cast metal posts; each has some benefits as well as drawbacks. This systematic review aims to compare and evaluate the survival rate and the resistance to fractures, the esthetic results, and the clinical effectiveness of glass fiber posts to cast metal posts. More specifically, using the basic keywords mentioned above and employing PubMed, Embase, and Scopus to search the literature, the present analysis was based on data from fourteen studies. Such studies included RCTs and cohort studies, in view of the fact that the selected studies were designed as such. The findings for this study show that glass fiber posts have a slightly higher survival rate in the range of 92. 8% compared to cast metal post in the range of 90% with the better esthetic results because of the properties of the glass fiber post combined with better distribution of the stress. This is not the case with cast metal posts which however display higher fracture resistances especially where there is need for high mechanical prowess. However, both materials can serve for clinical purposes, and the choice of one or another depends only on the concrete clinical situation and patients’ preferences. The review also ascertains the old as well as the new conformity, opportunities, and challenges of employing these materials in dental restorations.